Geodetic and hydrological research around Bulgarian Antarctic Base on Livingston island, Antarctica - Alexandrov, B.; Tzanovsky, Y. (Український антарктичний журнал, 2012)
This report displays the obstacles and specialties in doing geodetic and hydrographic works in the severe polar conditions of Antarctica, near Bulgarian Antarctic base on Livingston Island, South Shetland Islands. Surveying of the ice free rock passages by means of classical geodetic technology was made. The first hydrographical survey of a part of the South bay, near Bulgarian base was made too and displays the specialties in hydrographical works in polar conditions. For the implementation of the set goals, GPS, hydroacoustic and classical geodetic equipment were used. We represent results from a digital modeling of the relief of South Bay (next to BAB) and surveyed territory on Livingston Island. A geographic information system is used. Материал отражает трудности и особенности выполнения геодезических и гидрографических исследований в полярных условиях Антарктики в районе Болгарской антарктической базы (БАБ) на острове Ливингстон, Южные Шетландские острова. Средствами классической геодезической технологии выполнено картографирование свободных ото льда проходов в скалах. Сделан первый гидрографический снимок части акватории Южного залива в районе Болгарской антарктической базы, где отражены особенности гидрографической деятельности в полярных условиях. Для выполнения различных задач использованы GPS и гидроакустическая техника, а также конвенциональная геодезическая аппаратура. Представлены результаты цифрового моделирования рельефа дна и картографирования территорий в районе БАБ с использованием географической информационной системы. Матеріал відображає труднощі й особливості виконання геодезичних і гідрографічних досліджень у полярних умовах Антарктики в районі Болгарської антарктичної бази (БАБ) на острові Лівінгстон, Південні Шетландські острови. Засобами класичної геодезичної технології виконано картографування вільних від криги скельних проходів. Зроблено перший гідрографічний знімок частини акваторії Південної затоки в районі Болгарської антарктичної бази, на якому відображені особливості гідрографічної діяльності в полярних умовах. Для виконання різних завдань використано GPS та гідроакустичну техніку, а також конвенціональну геодезичну апаратуру. Представлено результати цифрового моделювання дна і картографування територій у районі БАБ з використанням географічної інформаційної системи.